ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI IMPLEMENTASI PROGRAM KOTAKU (KOTA TANPA KUMUH) DI KECAMATAN SEMARANG UTARA - Maida Sihombing, Lastiur; Hanani, Retna (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The KOTAKU (Kota Tanpa Kumuh) program is one of the strategic efforts of the Directorate General of Human Settlements in accelerating the handling of slum areas through the 100-0- 100 movement, namely 100% access to clean water, 0% slums and 100% proper sanitation in 2019. North Semarang District is one of the priority areas for slum upgrading in Semarang City. However, previous research on the KOTAKU program shows that KOTAKU targets have not been achieved. This study aims to analyze the factors that influence the implementation of the KOTAKU program in North Semarang District. The theory used is the implementation theory of George C. Edward III. There are five factors analyzed, namely communication, resources, disposition, bureaucratic structure and community support. The research approach is descriptive quantitative with 83 respondents of KOTAKU program implementers in North Semarang District. Data analysis using SmartPLS software version 4.0. The results showed that communication had a negative effect on implementation, amounting to 0.089. Resources have a positive and significant effect on implementation, amounting to 0.498. Disposition has a positive effect on implementation, amounting to 0.104. Bureaucratic structure has a negative effect on implementation, amounting to 0.067. Community support has a positive and significant effect on implementation, amounting to 0.108. Simultaneously, communication, resources, disposition, bureaucratic structure, and community support affect implementation by 0.702 or 70.2%, the rest (100%-72.5% =29.8%) is influenced by other factors outside the study. The suggestions given by the researcher are to ensure consistency and uniformity of information, add funding allocations to address incomplete slum problems, increase public trust to obtain optimal support from the community, and improve coordination and good cooperation between government agencies, BKM/KSM, and the community.